Pengembangan Media Video Pada Materi Degung Untuk Meningkatkan Pegetahuan Siswa Pada Pelajaran Seni Budaya Kelas V Di SDN Candraniti - Zidan Haidar, Mohammad; Nugraha, M. Fahmi; Permana, Rahmat (Sekolah Tinggi Ilmu Agama Islam Putra Galuh Ciamis, 2024)
This research aims to develop and determine the effectiveness of Degung Video Media in improving learning outcomes in class V Traditional Music material in elementary schools. The method used in this research is Research and Development type with 10 stages. However, this research is focused on stage 7. The research location is SDN Candraniti with subjects in grade 5 of elementary school. Data collection in this research was observation, interviews, questionnaires and tests. Meanwhile, the data analysis techniques used are qualitative analysis and quantitative analysis as well as analysis of student test results in the form of pretest and posttest. The results of this research are: (1) Degung Video media is suitable for use with the final media expert validation result being 3.75 in the